Orbital myosits in a patient with Behçet's disease - Fedrigo,Aiessa (2017)
Abstract The etiological diagnosis of orbital myositis (OM) is a challenge. Although it has been associated with previous infectious disease, diseases with autoimmune background, thyroidopathies or with paraneoplasic syndrome, most of them still remain as idiopathic. We describe here a case of OM uncovering a Behçet disease that is considered a rare cause for this kind of eye involvement.